(untitled) - Fetzer, Nancy (West Nyack, N.Y., 2000)
This practical resource gives primary teachers a collection of stimulating, tested learning center activities to teach and reinforce alphabet letters and their sounds. Helps children identify and spell words with ease!
Keywords: Early childhood education,English language,Giáo dục mầm non,Anh ngữ; Activity programs,Alphabet,Study and teaching (Early childhood),Chương trình hoạt động,Bảng chữ cái,Học tập và giảng dạy (Mầm non)